CREATION AND DEVELOPMENT OF CHEBOKSARY ENGINEERING CENTER FOR TRANSPORT AND AGRICULTURAL MACHINERY: THE PROJECT IMPLEMENTATION - R. I. Alexandrov; V. S. Grigoriev; E. N. Kadyshev (Высшее образование в России)
The key theme of the article is the development of engineering on the basis of higher educational institutions in the framework ofscientific knowledge and technology transfer in the real sector of the economy. The authors dwell on the activities of Cheboksary engineering centre for transport and agricultural machinery created on the basis of the Chuvash state University.